Pengembangan Alat Monitoring Suhu Multisensor Berbasis Mikrokontroler - Efendi, Rustam; Tando, Arjal; Padang, Welly; Aries, Mulhin; Herlina, Herlina (Badan Kerja Sama Teknik Mesin Indonesia, 2024)
one Adafruit MCP9808 sensor and five Adafruit MAX31856 thermocouple amplifiers. The design of this data logger allows temperature measurement in various applications, with a focus on monitoring room temperature. The prototype can be used in experiments, research, and industrial applications that require accurate temperature monitoring. This temperature data logger has the potential for wide-ranging applications in various contexts, with advantages in flexibility and affordability. The research validates that the MCP9808 sensor and MAX31856 amplifiers have a high level of accuracy in temperature measurements. The results of temperature measurements in a room environment indicated a temperature of approximately 29 ℃. This data logger design serves as a robust alternative for researchers who face limitations in acquiring standard commercial data loggers. The prototype has the potential to be a valuable tool in experiments and scientific research in various applications that demand precise temperature monitoring.